FACTORS RELATED TO THE PRESENCE OF AEDES AEGYPTI MOSQUITO LARVAE IN MENASAH KARIENG VILLAGE, LHOKNGA DISTRICT, ACEH BESAR REGENCY IN 2019 - Yusrina, Yusrina; Zulkifli, Zulkifli; Arlianti, Nopa (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: Lhoknga Health Center in 2016 there were 24 cases and in 2017 there were 33 cases and in 2018 there were 7 cases of DHF and in 2019 from January to May there were 7 cases in the Lhoknga Health Center area. This study aims to analyze the factors related to the presence of aedes aegypti mosquito larvae in Gampong Menasah Karieng, Lhoknga District, Aceh Besar Regency. Method: This research is descriptive analytical with Cross Sectional design with chi-square test. The population in this study were 224 families with toddlers, the sample size was 69 families, sampling was done by Proportional Random Sampling. Data analysis used bivariate and univariate analysis with chi-square statistical test. Result: Based on the results of the bivariate analysis study, it shows that there is a significant relationship between the presence of Aedes aegypti mosquito larvae and knowledge with a p value = 0.001, water disposal with a p value = 0.001, mosquito breeding places with a p value = 0.001, water reservoirs with a p value = 0.031, and waste disposal with a p value = 0.001. Recommendation: With this research, it is expected to always provide counseling on the implementation of PSN to the community so that the community understands and responds to PSN better, so that the implementation of PSN is appropriate. Periodic control of the environment is also carried out, as well as inviting the community to actively participate in preventing DHF and reporting cases that occur.